2018
DOI: 10.31887/dcns.2018.20.1/nsartorius
|View full text |Cite
|
Sign up to set email alerts
|

Depression and diabetes

Abstract: The comorbidity of mental and physical disorders is a major challenge for health care worldwide. Its prevalence is increasing and is likely to continue to grow due to the increase in life expectancy and a variety of other reasons. The comorbidity of depression and diabetes can be seen as a prototypical example of mental/physical comorbidity. The prevalence of both conditions is growing, and depression is twice as frequent in people with diabetes compared with those without diabetes. Health services are by and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(105 citation statements)
references
References 27 publications
2
77
0
3
Order By: Relevance
“…First, research suggests that classic psychedelics may facilitate healthy lifestyle changes associated with a beneficial impact on cardiometabolic risk factors (e.g., diet, alcohol and tobacco consumption, and exercise) 11 . Second, classic psychedelics administered in a safe and supportive setting have been shown to improve mental health conditions associated with cardiometabolic diseases 12 16 . Third, classic psychedelics have anti-inflammatory and immunomodulatory properties of importance for both mental and cardiometabolic health 17 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…First, research suggests that classic psychedelics may facilitate healthy lifestyle changes associated with a beneficial impact on cardiometabolic risk factors (e.g., diet, alcohol and tobacco consumption, and exercise) 11 . Second, classic psychedelics administered in a safe and supportive setting have been shown to improve mental health conditions associated with cardiometabolic diseases 12 16 . Third, classic psychedelics have anti-inflammatory and immunomodulatory properties of importance for both mental and cardiometabolic health 17 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…This increase has been particularly significant in women, who are reportedly twice as likely than men to suffer from this condition, with those between the ages of 45 and 54 representing the most vulnerable group [ 20 , 22 ]. Furthermore, if this data is correlated with diabetes mellitus, it has been shown that depression increases two to three-fold, tough many patients potentially remain undiagnosed [ 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there is ample evidence of metabolic abnormalities linked to schizophrenia and other psychiatric disorders, such as diabetes, cardiovascular disorder, and weight gain [ 45 , 46 , 47 , 48 , 49 ], it is still unclear whether these abnormalities co-occur with schizophrenia because of side effects from medications, lifestyle and diet, certain genetic predispositions, or possibly negative physiological impact of the psychiatric disorder. In this study, we have likewise found a metabolic signature associated with the severity of schizophrenia manifestation, which could also be linked to metabolic alterations found in common metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%